Mind the gap: the effect of cultural distance on mergers and acquisitions—evidence from glassdoor reviews - Marius Brede; Hannes Gerstel; Arnt Wöhrmann; Andreas Bausch (Review of Managerial Science, 2024)
This paper investigates the impact of differences in organizational culture on M&A outcomes during the transaction and post-merger integration phase. Using a state-of-the-art large language model, we construct a novel measure of organizational cultural distance based on employee reviews from Glassdoor.com covering 243 M&A deals from 2008 to 2021. First, we hypothesize and find that organizational cultural distance between acquirer and target firms lead to cultural frictions during the transaction and post-merger integration phases of the deal, which negatively affect short-term capital market reactions and long-term synergy gains. Second, our results suggest that cultural differences are positively related to the acquisition premium paid by the acquirer, supporting the hypothesis that cultural distance reduces the acquirer's ability to accurately assess the true value of the target, leading to an overestimation of the realizable synergy potential. Third, we show that cultural distance is negatively related to the long-term innovativeness of the acquiring firm. Specifically, our results suggest that patent growth and new product development, measured two years after the deal, are significantly lower for firms that acquire a culturally distant target. We then examine the underlying cultural dimensions that drive these effects. Consistent with previous studies, we find that performance effects are driven by differences in market orientation, while innovation effects are driven by differences in hierarchy or adhocracy orientation, depending on whether innovation is measured in terms of tangible or intangible assets. Our findings contribute to the broad M&A literature and have practical relevance for firms engaged in M&A transactions.
Keywords: M14; G34; C45; 650; Organizational culture; Cultural distance; Mergers and acquisitions; M&A performance; Innovation; Natural language processing